Development of a user friendly authoring tool for compact disc recorders - Lim, Theng Ang. (2008)
Many changes have been afoot in the CD-R for the last decade. The CD-R recorder used to be a proprietary luxury item that only a software developer would own due to its price of more than S$25,000. With the near-universality of CD-ROM drives, no other medium can compete with the CD-R in terms of sharing, transporting, or archiving information. The CD-R bundle comes with a hardware and software package that will provide the authoring environment for the CD-R drive. Unfortunately, a lot of authoring software is yet to be friendly enough for general user.